Educational Leadership Challenges in the 21st Century: Closing the Achievement Gap for At-Risk Students - Randall S. Vesely (Educational Considerations, 2010)
The purpose of this special issue is twofold: To explore the challenges educational leaders face in addressing the achievement gap for at-risk students; and to seek solutions.